STRATEGI GURU DALAM MENGATASI KESULITAN BELAJAR SISWA KELAS 2 MI AL MAARIF 02 SINGOSARI - Lestari Milacandra; Mohammad Afifulloh; Muhammad Sulistiono (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
AbstractThis research was conducted to determine the teacher’s strategi in overcoming learning difficulties, especially in grade 2 students of MI Al Maarif 02 Singosari. This research uses interview, observation and documentation methods. In this study researchers used interview instruments. At this time most students are not aware of what learning difficulties are experienced. Strategy is the main goal to overcome learning difficulties in students so that students learning in the classroom can be achieved in accordance with educational goals. The implementation of strategies used by teachers is not as long as it runs smoothly, there are obstacles from family environment factors, the school environment. In connection with this, researchers sought information on strategies that were suitable in overcoming the learning difficulties of MI Al Maarif 02 Singosari students. Keywords : Strategy, Difficulty Learning